2020
DOI: 10.1177/1528083720960743
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid composite laminates reinforced with flax-basalt-glass woven fabrics for lightweight load bearing structures

Abstract: An experimental investigation on the mechanical performance of interlayer hybrid flax-basalt-glass woven fabrics reinforced epoxy composite laminates has been performed. The tensile, flexural, in-plane shear, interlaminar shear, bearing, and impact properties of the fabricated laminates were investigated. Test specimens were fabricated using vacuum bagging process. Failure modes of all specimens were recorded and discussed. Results proved that the mechanical properties of flax-basalt-glass hybrid laminates are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 88 publications
2
11
0
Order By: Relevance
“…2 e. According to the data given by the supplier, curing conditions of Kemapoxy 150 RGL are 8 h initial setting time, 24 h final setting time, and 7 days’ full hardness time. Attia et al 61 and Awd Allah et al 62 adapted the above-mentioned curing conditions. The manufactured hybrid pipes were visually examined for material flaws and geometrical abnormalities after curing.…”
Section: Methodsmentioning
confidence: 99%
“…2 e. According to the data given by the supplier, curing conditions of Kemapoxy 150 RGL are 8 h initial setting time, 24 h final setting time, and 7 days’ full hardness time. Attia et al 61 and Awd Allah et al 62 adapted the above-mentioned curing conditions. The manufactured hybrid pipes were visually examined for material flaws and geometrical abnormalities after curing.…”
Section: Methodsmentioning
confidence: 99%
“…Because untreated J-fiber has smooth surfaces, epoxy and untreated J-fiber have low interfacial compatibility. Attia et al 26 found that weak interaction causes a lot of gaps in the fiber-matrix interfaces.
Figure 7.(a) Flexural strength, (b) modulus, and (c) strain of jute (J)-basalt (B)/epoxy composite laminates.
…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 displays the constituent materials’ characteristics. Many authors in the literature Ahmed and Vijayarangan, 43 Amuthakkannan et al, 53 Sanjay and Yogesha, 54 Attia et al, 26 and Gangappa and Kulkarni 48 used the as received (untreated) natural fibers without any treatment. Therefore, no surface treatment of any type, including washing, was applied to B-fiber and J-fiber used in this study.
Figure 1.Surface images of (a) basalt, and (b) jute fabrics used in this study.
…”
Section: Resources and Techniquesmentioning
confidence: 99%
“…Tensile, flexural, and in‐plane shear tests were conducted at a crosshead speed of 2 mm/min, as per the corresponding ASTM test standards 50–52 . The details of the tests and the used equations can be found in reference 53–55.…”
Section: Testingmentioning
confidence: 99%